LEGAL PROTECTON OF WOMEN CIVIL CERVANTS OF GENDER DISCRIMINATION IN THE ERA OF REGIONAL AUTONOMY IN THE DISTRICT ADMINISTRATION SUMBAWA - WEST NUSA TENGGARA - Dahlan, Syarif (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 1 (2013), 2013)
Aware of gender discrimintaion of women and students of women in different countries, so they protest and movement finally manage to do some conference that have produced Convention On The Elimination Of All Form Of Diskrimination Against Women   (CEDAW). Indonesia has ratified CEDAW with Law No. 7, 1984. But until now gender discrimination still occurs in all facets of life and society. One of them is a fimale civil servant in Sumbawa regency. Discrimination that has accurred not given the opportunity to accupy the fimale civil servant echelon-echelon II and III. In connection with the second echelon echelon II or III on Sumbawa Regency :      1) What are the forms of gender discrimination against fimale civil servants. 2) What factors are causing it, and 3) What is the form of legal protection against civil servants are women from gender discrimination. This study includes empirical legal research aims to determine the effectiveness of the law and the legal vacuum in the administration and management of government, particularly in women civil servants in positions echelon II or III. Dates collected were analyzed with descriptive analytic techniques. These form of discrimination against women in Sumbawa civil servants include marginalization and subordination, the factors that cause it was a mistake in the interpretation and implementation   gender equality, influence the understanding and application of Islamic teachings, political and cultural factors shame, geographical factors tough, close relationship with the ruling factor, factor in the civil servants streotif women and a heavier workload factor for women. Moderate forms of legal protection can be seen from the substance of the law, the legal structure and legal culture.
Keywords: Legal protection; gender; fimale civil servants; regional outonomy